Influence of the Carbon Black Dispersing Process on the Microstructure and Performance of Li‐Ion Battery Cathodes. Issue 2 (29th April 2019) - Mayer, Julian Kristoffer; Almar, Laura; Asylbekov, Ermek; Haselrieder, Wolfgang; Kwade, Arno; Weber, André; Nirschl, Hermann
Abstract : The influence of the dispersion process and the carbon black (CB) particle size on the resulting structure and, hence, on the properties of lithium‐ion battery cathodes is investigated. N ‐methyl‐2‐pyrrolidone‐based cathode slurries with 95.5 wt% LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622) and a high mass content (82.5 wt%) are processed in a planetary mixer PMH10 from NETZSCH with varying high‐speed stirrer tip speeds. Particle size analyses are carried out to measure the CB particle size at different time steps of the dispersion process. The resulting cathodes are characterized to determine mechanical and electrical properties. The microstructure of chosen electrodes is reconstructed and quantified by focused ion beam/scanning electron microscopy tomography and correlated with experimental data. In addition, discrete element method simulations are used for a deeper understanding of the dispersion process and breakage of CB aggregates. Correlations between process, structure, and properties of lithium‐ion battery cathodes are revealed. Abstract : The microstructure of lithium‐ion battery electrodes is determined by (dispersion) process and formulation parameters, which can be directly correlated with mechanical, electrical, and electrochemical properties. Accordingly, to optimize the properties of the electrode and, hence, the battery, the microstructure of the electrode must be improved. Therefore, carbon black is an important structuring component.